2021
DOI: 10.1242/jeb.242256
|View full text |Cite
|
Sign up to set email alerts
|

Mantis shrimp identify an object by its shape rather than its color during visual recognition

Abstract: Mantis shrimp commonly inhabit seafloor environments with an abundance of visual features including conspecifics, predators, prey, and landmarks used for navigation. While these animals are capable of discriminating color and polarization, it is unknown what specific attributes of a visual object are important during recognition. Here we show that mantis shrimp of the species Neogonodactylus oerstedii are able to learn the shape of a trained target (p=0.048). Further, when the shape and color of a target which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Later, Thoen et al [25] trained members of a different species, Haptosquilla trispinosa, to discriminate paired spectral lights from each other. Most recently, Patel et al [34] demonstrated that individuals of N. oerstedii can discriminate identical objects of different colours (red versus green). All these tests involved a food reward, but it seems likely that stomatopods also use their colour vision in species recognition and in signalling, although these situations have not yet been investigated.…”
Section: Colour Vision In the Visible Light Rangementioning
confidence: 99%
See 1 more Smart Citation
“…Later, Thoen et al [25] trained members of a different species, Haptosquilla trispinosa, to discriminate paired spectral lights from each other. Most recently, Patel et al [34] demonstrated that individuals of N. oerstedii can discriminate identical objects of different colours (red versus green). All these tests involved a food reward, but it seems likely that stomatopods also use their colour vision in species recognition and in signalling, although these situations have not yet been investigated.…”
Section: Colour Vision In the Visible Light Rangementioning
confidence: 99%
“…When associating coloured shapes with food, the stomatopod N. oerstedii learns the shapes' colours, but if the shape and colour are placed in conflict, individuals of this species turn to shape as the primary identifier [34]. In another example of shifting modes of visual analysis, individuals of G. smithii reduce the use of visual displays in dim light, relying on chemoreception when communicating [78].…”
Section: What Is the Function Of Colour Vision In Mantis Shrimps?mentioning
confidence: 99%
“…As sunlight traverses the Earth's atmosphere, it establishes a stable polarization distribution pattern across the entire sky due to the scattering effects of atmospheric molecules and aerosol particles [4][5][6]. Biological studies have indicated that organisms such as mantis shrimp [7], octopuses [8], locust [9], and desert ants [10] can utilize their unique visual structures to perceive the polarization patterns of the entire sky, employing this information for self-orientation. Inspired by biomimetic navigation mechanisms, polarized navigation has demonstrated advanced performance in unmanned aerial vehicles [11,12], unmanned ground vehicles [13][14][15], and other navigation domains.…”
Section: Introductionmentioning
confidence: 99%